Achievements of the national education standards and education quality assurance implementations in vocational high schools in D.I. Yogyakarta - Wahyuni, Indah; Darmono, Darmono; Putra Pratama, Galeh Nur Indriatno (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
In the world of education, the issues faced cannot be separated from the quality of educational services and the public's view of an educational unit. Reviews related to the implementation of National Education Standards and Education Quality Assurance can be used to find out the good and bad of the institutions so that it can help the public provide a positive view. This research aims to analyze the implementation achievements of (1) Content Standards and Process Standards; (2) Assessment Standards; (3) Facilities and Infrastructure Standards; (4) Management Standards; (5) Financing Standards; and (6) Education Quality Assurance in several Vocational High Schools in D.I. Yogyakarta. This research used a descriptive quantitative approach, and the research samples were chosen through a probability sampling system, with questionnaires as the data sample technique. There are six instruments used, which are Content Standards and Process Standards, Assessment Standards, Facilities and Infrastructure Standards, Management Standards, Financing Standards, and Education Quality Assurance. The data is examined through descriptive statistical tests and data percentages that will be used later to find out the calculation result. The result of the research suggests that the achievement of the implementation of Assessment Standards reaches 85,74%, Management Standards 85,49%, Financing Standards 82,77%, Content Standards and Process Standards 82,44%, Education Quality Assurance 80,21%, and lastly, Facilities and Infrastructure Standards 78,85%. The research shows that Assessment Standards are the highest achievement of all, while the lowest standard was seen on Facilities and Infrastructure Standards.